Manajemen Strategi untuk Meningkatkan Mutu Lembaga Pendidikan Islam - Iqbal Fawaidul Muhsinin; Sedya Sentosa; Fina Umu Rif'Athi (Studia Manageria, 2023)
Final exam scores are not the only indicator of the quality of educational outcomes in today's society. Society is starting to observe, in terms of the quality of education, the extent to which college graduates can integrate into everyday life. In this article the researcher will explain strategic management to improve the quality of Islamic educational institutions. This article is written using the library research method. Library study is a data analysis method using references in the form of books, journals, notes or the results of previous research. Based on the results of research that researchers have conducted, by carrying out strategic management, educational institutions have received real benefits, through strategic management these educational institutions have obtained effective strategies in determining their direction or goals. Implementation of strategic management can be carried out using SWOT analysis. With a SWOT analysis, educational institutions can carry out strategic steps, so that they can improve the quality of educational institutions